Design, Implementation and Assessment of BPSK and QPSK PAPR over OFDM signals using LimeSDR - Kagande, Tinashe (Department of Electrical Engineering, 2024)
Modern day communications required efficient and affordable wireless communication techniques. Traditional wireless communication systems involved a lot of hardware for each component within the system. Software Defined Radios (SDR) became popular and were a major area of research as they provided a highly adaptive software solution to the traditional analog hardware solutions that were commonly implemented for communication systems. The benefits of using SDRs outweighed those of traditional analog hardware by a significant margin, hence so much research and development was pursued in this area. SDRs offered upgradability and adaptation often without needing to change the hardware, giving them the edge over traditional hardware approaches that needed replacement for upgrades. With Orthogonal Frequency Division Multiplexing (OFDM) being one of the most popular modulation techniques for Next Generation Networks (NGN), it was important to understand how best it could be delivered using low-cost SDRs. The biggest challenge of OFDM multiplexing was high PAPR, which could necessitate expensive circuitry for ADC/DAC components of an SDR solution. OFDM signals were popularly modulated either by Binary Phase Shift Keying (BPSK) or Quadrature Phase Shift Keying (QPSK), which then brought in the question “What was their contribution to Peak-to-Average Power Ratio (PAPR) in an OFDM system?”. Consequently, this project compared BPSK and QPSK in terms of PAPR in OFDM signals. A personal computer was used to host GnuRadio-based prototypes on which an OFDM system was developed using OFDM blocks inbuilt in the software. LimeSDR hardware was used to sample radio waves. A LimeSDR block was implemented in GnuRadio to interconnect with the LimeSDR module. An OFDM transceiver was designed in GnuRadio, and the code developed for this project was also open source. GnuRadio was selected specifically for its open-source flexibility, that allowed adaptability and the prospect to experiment with code, which was expected to be of benefit for future work. For this project, pre-selected data stored on the host PC, was transmitted from the OFDM transmitter through the LimeSDR antennas and received by the Lime SDR antennas, then demodulated and saved in a different folder on the host PC. Once this was achieved, user interface facilities were added to facilitate use and testing. Results from the testing demonstrated the compatibility of LimeSDR and GnuRadio and showed significant differences between a BPSK modulated signal and QPSK modulated signal in terms of PAPR. This project aimed to provide contributions to the radio and wireless communication field as well as being supportive towards other ongoing projects taking place in the UCT Electrical Engineering Department that connected to pertinent considerations for 5G and IoT wireless remote sensing solutions.